The application of “write it right!” board game in an esl writing classroom: a study on students’ perspectives - Lin, Nur Maizura; Zahari, Nur Syamimi; Md Supie, Hawa Syamsina; Rosly, Rosdin (GADING Journal for the Social Sciences, 2024)
Board games have become an indispensable tool in teaching and learning nowadays. Many learning instructors have chosen to use board games as an instrument to enhance their students’ language learning process. By incorporating games into the learning process, students are exposed to experiential learning. In this study, the focus is on incorporating board games in a language classroom with a specific focus on writing skills. The objectives of this study are twofold. They are to investigate students’ perceptions of using the “Write It Right!” (WIR) board game as a medium to assist them in the ESL writing classroom and to determine if the students’ perceptions differ between genders. The WIR board game was used during a writing class session for diploma students at a local university. Upon completion of using the board game, students were required to complete a survey to gauge their perceptions of using the board game as a tool in language learning. The findings discovered a positive outcome on the application of board games in the language classroom. It is recommended that language instructors embed board games into their writing classrooms to encourage and enhance students’ writing skills.